2016
DOI: 10.5424/fs/2016252-08062
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of biomass and carbon pools in disturbed and undisturbed oak forests in Tunisia

Abstract: Aim of the study. To estimate biomass and carbon accumulation in a young and disturbed forest (regenerated after a tornado) and an aged cork oak forest (undisturbed forest) as well as its distribution among the different pools (tree, litter and soil).Area of study. The north west of Tunisia Material and methods. Carbon stocks were evaluated in the above and belowground cork oak trees, the litter and the 150 cm of the soil. Tree biomass was estimated in both young and aged forests using allometric biomass equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…An important research effort has been undertaken over the last decade to improve forest carbon estimations and to determine the effects of management on carbon sequestration in the Mediterranean area, as described this review and summarized in Table 4. Most of this research has been done in the northern and western areas of the Mediterranean region, but more research along these lines is currently in progress in southern and eastern areas (e.g., Durkaya et al, 2013;Makineci et al, 2015;Oubrahim et al, 2015;Zribi et al, 2016). In spite of this effort, there are still certain gaps in our knowledge that need to be addressed in order to fulfill the requirements of our society.…”
Section: Perspectives and Challengesmentioning
confidence: 99%
“…An important research effort has been undertaken over the last decade to improve forest carbon estimations and to determine the effects of management on carbon sequestration in the Mediterranean area, as described this review and summarized in Table 4. Most of this research has been done in the northern and western areas of the Mediterranean region, but more research along these lines is currently in progress in southern and eastern areas (e.g., Durkaya et al, 2013;Makineci et al, 2015;Oubrahim et al, 2015;Zribi et al, 2016). In spite of this effort, there are still certain gaps in our knowledge that need to be addressed in order to fulfill the requirements of our society.…”
Section: Perspectives and Challengesmentioning
confidence: 99%
“…Zribi et al [49] found that aged trees have the largest biomass and thus the highest capacity of CS but less potential for future CS in comparison to young trees, which have not only rapid growth but also more CS capability. The consensus found that as a tree grows older due to an increase in DBH and height, a constant increase in biomass is attained and the tree thus becomes a good carbon reservoir [50].…”
Section: Carbon Sequestration and Characteristics Of Treesmentioning
confidence: 99%
“…Instrumen yang spesifik diperlukan guna menentukan nilai ekonomi berdasarkan fungsi tersebut. Nilai karbon tersimpan dapat dinilai secara ekonomi melalui nilai ekonomi hutan secara keseluruhan (Tietenberg & Lewis, 2009 Potensi karbon dihitung menggunakan metode AR-AMS 0007 versi 02 untuk jumlah karbon di dalam tanah (underground biomass) dan karbon di atas permukaan tanah (above ground biomass) dihitung dengan menggunakan persamaan allometric biomass (Driver, 2012;Hairiah & Rahayu, 2007;Ketterings, Coe, van Noordwijk, Ambagau', & Palm, 2001;Zribi et al, 2016). Persamaan allometric biomass yang digunakan merujuk pada Ketterings et al (2001) dan dirumuskan sebagai berikut: 2.62 Keterangan: ρ = Massa jenis kayu (kg per m 3 ); D = Diameter pohon (cm)…”
Section: Pendahuluanunclassified